High capacity metal and mixed metal borohydride ammoniates for hydrogen energy storage applications - Prosser, J.L. (2024)
This thesis explores the promising class of metal borohydride ammoniates and mixed metal borohydride ammoniates (MBA and MMBAs) for hydrogen storage applications. Although possessing high hydrogen (H2) gravimetric capacities (7 ≤ wt.% ≤ 18) and low dehydrogenation temperature (< 200 ◦C), the H2 release is often coupled with the release of ammonia (NH3). Suppressing the NH3 release is vital for applications requiring high purity H2. In order to direct work to explore new MBA/MMBAs that preferentially release H2, the gas evolution characteristics were compared with a variety of properties of known MBA/MMBAs. It is observed that a decreasing ionic radii / increasing charge density of the metal cation of the MBA/MMBA results in preferential H2 release. If the metal cation has an ionic radii < 0.61 Å and/or charge density value ≥ 200 C mm-3 , the MBA/MMBA is shown to release H2 preferentially in comparison to NH3. The atom interaction analysis conducted on the B-H bond length and intramolecular B-N distance of MBAs with a range of NH3 ligands (Ce, La, Mn and Y) indicated that a lower number of NH3 ligands results in shorter B-H bond lengths, B-N distances and a preference to release H2. It is suggested that the shorter B-H bond length leads to a more negatively charge hydridic atom (Hδ- ) in the BH4 unit, which is more attracted to the protic atom (Hδ+) in the NH3 ligand and a shorter B-N distance allows longer duration of the Hδ+ and Hδ- being in close proximity. Both would aid the dehydrogenation reaction; H2NHδ+... δ-HBH3.